PRAKTIK RAHN PADA MASYARAKAT DESA SELAT REMIS KABUPATEN KUBU RAYA DALAM PERSPEKTIF KOMPILASI HUKUM EKONOMI SYARIAH - Rafi'ah Rafi'ah; Rasiam Rasiam; Nur Rahmiani (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2022)
This research was motivated by an interesting phenomenon that occurred in the West Kalimantan region, especially in the Remis Strait Village area, Teluk Pakedai District, Kubu Raya Regency, namely the existence of a pawn where it contains sharia values. The practice in question is the practice of rahn among the people of Selat Remis Village from the Perspective of the Sharia Economic Law Compilation (KHES). The purpose of this study is to analyze the practice of rahn among the people of Selat Remis Village from the Perspective of the Compilation of Sharia Economic Law (KHES). This research method is qualitative with a sociological-empirical approach. The primary data sources themselves are rahin (a pawnee) and murtahin (a pawnee). Meanwhile, secondary data was obtained from various sources including books and journals. The argument of this research is that the practice of pawning that occurs refers more to the habits and traditions that apply in the community. Based on the data obtained, it can be concluded that the practice of pawning that occurs between the people of the Remis Strait only aims to help each other with the principle of kinship and mutual trust. This pawn in harmony and terms has complied with the provisions of the KHES.